Cover Image. (11th April 2019) - Saito, Atsushi; Bizenjima, Takahiro; Takeuchi, Takahiro; Suzuki, Eiichi; Sato, Masahiro; Yoshikawa, Kouki; Kitamura, Yurie; Matsugami, Daisuke; Aoki, Hideto; Kita, Daichi; Imamura, Kentaro; Irokawa, Daisuke; et al.
Abstract : The cover image is based on the Randomized Clinical Trial Treatment of intrabony periodontal defects using rhFGF‐2 in combination with deproteinized bovine bone mineral or rhFGF‐2 alone: A 6‐month randomized controlled trial by Atsushi Saito et al., DOI: 10.1111/jcpe.13086